Progress in ZnO Acceptor Doping: What Is the Best Strategy? - Judith G. Reynolds; C. Lewis Reynolds (Advances in Condensed Matter Physics)
This paper reviews the recent progress in acceptor doping of ZnO that has been achieved with a focus toward the optimum strategy. There are three main approaches for generating p-type ZnO: substitutional group IA elements on a zinc site, codoping of donors and acceptors, and substitution of group VA elements on an oxygen site. The relevant issues are whether there is sufficient incorporation of the appropriate dopant impurity species, does it reside on the appropriate lattice site, and lastly whether the acceptor ionization energy is sufficiently small to enable significant p-type conduction at room temperature. The potential of nitrogen doping and formation of the appropriate acceptor complexes is highlighted although theoretical calculations predict that nitrogen on an oxygen site is a deep acceptor. We show that an understanding of the growth and annealing steps to achieve the relevant acceptor defect complexes is crucial to meet requirements.